2019
DOI: 10.1186/s12891-019-2833-4
|View full text |Cite
|
Sign up to set email alerts
|

Gluteus medius muscle function in people with and without low back pain: a systematic review

Abstract: IntroductionGlobally, low back pain (LBP) is one of the greatest causes of disability. In people with LBP, dysfunction of muscles such as the gluteus medius have been demonstrated to increase spinal loading and reduce spinal stability. Differences in gluteus medius function have been reported in those with LBP compared to those without, although this has only been reported in individual studies. The aim of this systematic review was to determine if adults with a history, or current LBP, demonstrate differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 44 publications
2
20
1
Order By: Relevance
“…Our findings of lower gluteus medius mean and peak amplitude in participants with planus foot types are in contrast to previous research that has shown higher levels of activity in people with chronic low back pain and pronated feet [5]. However, a recent systematic review found the relationship between low back pain and gluteus medius muscle activity to be inconclusive [42]. Another systematic review investigating the effect of foot posture on lower leg muscle activity during gait found some evidence to show that in people with planus type feet, greater levels of anti-pronator muscle activity (e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings of lower gluteus medius mean and peak amplitude in participants with planus foot types are in contrast to previous research that has shown higher levels of activity in people with chronic low back pain and pronated feet [5]. However, a recent systematic review found the relationship between low back pain and gluteus medius muscle activity to be inconclusive [42]. Another systematic review investigating the effect of foot posture on lower leg muscle activity during gait found some evidence to show that in people with planus type feet, greater levels of anti-pronator muscle activity (e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…Several musculoskeletal factors related to movement and/or muscular activity impairments have been highlighted in NSCLBP patients compared to asymptomatic participants 10 . Kinematic parameters such as range of motion, segment coordination or movement variability 11 , 12 , as well as electromyographic parameters such as maximal activity, timing activity or fatigability 13 , 14 , are regularly measured in NSCLBP population. However, due to methodological differences and/or the heterogeneity of the NSCLBP population, some studies reported contradictory findings 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Gmed weakness may eventually lead to loss of dynamic lateral stability of the pelvis and lower back which may lead to the development of LBP. 25 To our knowledge based on the literature search, no studies have been done to compare Gmed muscle activity in NSCLBP and healthy individuals measured with the hip abducted in side-lying position. The primary aim of this present study was to compare the difference of Gmed muscle activation in NSCLBP and healthy individuals using SEMG.…”
Section: Discussionmentioning
confidence: 99%